Stability of a Logarithmic Functional Equation in Distributions on a Restricted Domain - Jaeyoung Chung; Prasanna K. Sahoo (Abstract and Applied Analysis)
Let be the set of real numbers, , , and . As classical and versions of the Hyers-Ulam stability of the logarithmic type functional equation in a restricted domain, we consider the following inequalities: , and in the sectors . As consequences of the results, we obtain asymptotic behaviors of the previous inequalities. We also consider its distributional version , where , , , , , and the inequality means that for all test functions .